Aloyr Queiroz de Araujo: arquivos, redes de sociabilidade, estratégicas e táticas na constituição da Educação Física capixaba (1946-1970) - Eller, Marcelo Laquini (2019)
The study presents the result of the investigation that sought to understand part of the history of Physical Education of Espírito Santo, through the memory and history of the personal archive of Professor Aloyr, an intellectual who acted tactically and strategically at the forefront of the field of Physical Education between the middle of the 20th century. Aloyr remained for two decades as director of the main governing bodies of Physical Education in the state of Espírito Santo and his action to intervene, record and narrate the sporting life in Espírito Santo, allows us to understand the practices and development of actions political and pedagogical that he undertook as teacher, manager and one of the main articulators of a training project for the Physical Education course of Espírito Santo. The projects developed for the sport, the academic activities, the actions as journalist and activist in favor of a scientific formation of the professor of Physical Education, are related in his books, in the lectures given and in the chronicles that he performed. All these strategies of writing and synthesis are for us considered as representations, circulated and shared with their community of readers and listeners, and which today constitute as a memory of Physical Education, guarded as a monument of a life, as a legacy that speaks of the past and of man in time. As a theoretical reference, he uses the propositions of Roger Chartier with the concepts of representation and practices of representation, Carlo Ginzburg with the indicia model, Jaques Le Goff with the concepts of document and monument, Marc Bloch directs us the historiographic perspective of the historical narrative, Jean Françoise Sirinelli, with the concept of social network and Michel de Certeau with the concepts of strategy and tactics. As a source, it makes use of official documents, newspaper clippings, books, articles, magazines, collections; official documents from the Cefd / Ufes permanent archive and interviews with historical actors. It is concluded that the personal archive of Aloyr was constructed with intentionalities and the explicit need of this historical actor to record his memory for posterity and the analysis of his documents helped to understand part of the history of Education Capixaba physics.